1996
DOI: 10.1016/s1046-199x(96)90078-0
|View full text |Cite
|
Sign up to set email alerts
|

Fragrance contact dermatitis: A worldwide multicenter investigation (Part I)

Abstract: The age at which patients with perfume allergy present for evaluation is similar to that of other contactants. Atopic individuals may be overrepresented in this group of patients. Face involvement is likely. White persons are more likely to react to fragrance mix, whereas in Asian patients benzyl salicylate was a more frequent allergen. Fragrance mix corrected with 85.6% of positive responses to fragrance ingredients. The addition of ylang ylang oil, narcissus oil, and sandalwood oil to fragrance mix would be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(42 citation statements)
references
References 18 publications
2
37
1
2
Order By: Relevance
“…The FM PT-positive rate was 15.9% in our study. Previous studies showed that the prevalence of FM reactions in PT clinics worldwide was high and often ranked among the top 3 allergens (11). In dermatitis patients evaluated by patch testing, reactions to FM have ranged from 5.9% in Slovenia to 19.5% in Hong Kong (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…The FM PT-positive rate was 15.9% in our study. Previous studies showed that the prevalence of FM reactions in PT clinics worldwide was high and often ranked among the top 3 allergens (11). In dermatitis patients evaluated by patch testing, reactions to FM have ranged from 5.9% in Slovenia to 19.5% in Hong Kong (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Coumarin, an ingredient in cosmetics and fragrances, was chosen as the reference chemical, since there is a controversy as to whether coumarin is a contact allergen involved in fragrance allergy. Indeed, coumarin allergy, defined by positive skin patch tests, was observed in up to 6.8% of patients with ACD [9,10,11,12,13]. Moreover, it was shown that coumarin was endowed with irritant properties at the concentration of 8% [13].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of fragrance mix (FM) reactions in patch test clinics worldwide is high and often ranks among the top 3 allergens [3]. …”
Section: Introductionmentioning
confidence: 99%